Early versus Traditional Oral Feeding after Elective Intestinal Stoma Closure - Syed Md Azim Uddin; Md Matiar Rahaman Khan; Syed Md Muhsin; Shahed Mohammed Anwar; Shoibul Karim; Samiha Binte Ahsan (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Postoperative feeding protocols following elective intestinal stoma closure remain debated, with limited consensus on optimal timing. Early enteral feeding is hypothesized to enhance recovery, reduce complications, and lower healthcare costs, particularly in resource-limited settings. The study aimed to compare the morbidity and outcome of early versus traditional oral feeding after elective intestinal stoma closure. Materials and methods: This quasi-experimental study compared the outcomes of early oral feeding (Within 12–24 hours post-surgery) versus traditional feeding (Initiated after ileus resolution) in 88 patients undergoing elective intestinal stoma closure (Ileostomy/colostomy) in the Department of Surgery, Chittagong Medical College Hospital from January 2022 to December 2022. Patients were divided into Group A (Traditional feeding, n=44) and Group B (Early feeding, n=44). Postoperative outcomes included bowel function recovery, complications (Fever, cough, wound infection, anastomotic leakage) and hospital stay. Results: Group B had significantly lower postoperative complications on days 3, 5 and 7. By day 3, Group A had higher rates of fever (61.4% vs. 20.5%) wound infection (25% vs. 9.1%), and cough (65.9% vs. 31.8%), all statistically significant (p<0.05). Anastomotic leakage occurred in 4.5% of Group A versus none in Group B, though statistically insignificant (p=0.153). Early feeding correlated with faster bowel function recovery: earlier bowel sounds, flatus and stool passage (p<0.001). Hospital stay was significantly shorter in Group B (4.02± 1.13 days vs. 7.95 ± 2.34 days, p<0.001). Conclusion: The study concluded that early oral feeding after elective stoma closure is safe, accelerates bowel recovery, reduces complications, and shortens hospital stay. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 31-35